The impact of positive youth development (5C) on the wellbeing of youth in Selangor, Malaysia - Muhamad, Nur Syafiqah; Ma’rof, Aini Azeqa; Abdullah, Haslinda (Human Resource Management Academic Research Society, 2024)
This study investigates the impact of Positive Youth Development (PYD) attributes, specifically Competence, Confidence, Connection, Character, and Caring, which are together referred to as the 5Cs, on the overall well-being of young individuals. The research examines the impact of these qualities on the psychological well-being of young individuals in an educational context, using t-tests, correlation analyses, and regression analysis. Initial t-tests revealed that there were no statistically significant gender differences in well-being, which establishes a stable starting point for subsequent analyses. The correlation analysis demonstrated significant positive correlations between Confidence, Connection, Character, Caring, and well being, with Caring exhibiting the most robust association. Surprisingly, there was no significant correlation found between Competence, indicating that its influence may be influenced by other characteristics. The regression analysis identified Caring as the most influential factor in predicting well-being, demonstrating a strong and positive impact. In contrast, Confidence had a negative beta, indicating intricate dynamics that could involve the influence of overconfidence effects. The regression model indicated that there was no significant predictive value of Connection and Character, despite a strong correlation. This suggests that there may be other unmeasured variables that are influencing the results. The results emphasise the need of prioritizing emotional and interpersonal abilities in programmes aimed at fostering the well-being of young individuals. The findings support the implementation of a comprehensive strategy that promotes empathy and social relationships in addition to enhancing abilities and self-assurance. Future research should incorporate longitudinal designs and incorporate more objective measures in order to further comprehension of these linkages. This research enhances the field by highlighting the diverse effects of positive youth development (PYD) traits on well-being and advocating for holistic approaches to development that address the emotional and social needs of young people.